Dexmedetomidine alleviates inflammatory response and oxidative stress injury of vascular smooth muscle cell via α2AR/GSK-3β/MKP-1/NRF2 axis in intracranial aneurysm - Ze Zhang; Xiue Mu; Xiaohui Zhou (BMC, 2022)
Abstract Vascular smooth muscle cell (VSMC) phenotypic modulation regulates the initiation and progression of intracranial aneurysm (IA). Dexmedetomidine (DEX) is suggested to play neuroprotective roles in patients with craniocerebral injury. Therefore, we investigated the biological functions of DEX and its mechanisms against IA formation and progression in the current study. The rat primary VSMCs were isolated from Sprague-Dawley rats. IA and superficial temporal artery (STA) tissue samples were obtained from patients with IA. Flow cytometry was conducted to identify the characteristics of isolated VSMCs. Hydrogen peroxide (H2O2) was used to mimic IA-like conditions in vitro. Cell viability was detected using CCK-8 assays. Wound healing and Transwell assays were performed to detect cell motility. ROS production was determined by immunofluorescence using DCFH-DA probes. Western blotting and RT-qPCR were carried out to measure gene expression levels. Inflammation responses were determined by measuring inflammatory cytokines. Immunohistochemistry staining was conducted to measure α2-adrenergic receptor levels in tissue samples. DEX alleviated the H2O2-induced cytotoxicity, attenuated the promoting effects of H2O2 on cell malignancy, and protected VSMCs against H2O2-induced oxidative damage and inflammation response. DEX regulated the GSK-3β/MKP-1/NRF2 pathway via the α2AR. DEX alleviates the inflammatory responses and oxidative damage of VSMCs by regulating the GSK-3β/MKP-1/NRF2 pathway via the α2AR in IA.